Editor's Note - Ellen R. Cohn; Jana Cason (International Journal of Telerehabilitation)
The current issue of the International Journal of Telerehabilitation (IJT) contains original research evaluating the efficacy of telerehabilitation; an evaluation of a telerehabilitation system for community based research; and work that examines users’ perceptions of the privacy and security of the three top used consumer-based, free Voice and video over the Internet Protocol (VoIP) software systems (e.g., Skype  and others) used by health care providers to deliver therapeutic services via telerehabilitation. Two Brief Communications authored by speech-language pathologists present the possibilities for significant telehealth related cost-savings when telepractice is implemented in clinical practice.  Finally, this issue presents a report generated by a working group within the American Telemedicine Association’s Telerehabilitation Special Interest Group, and announcements from the American Telemedicine Association and the International Society for Augmentative and Alternative Communication (ISAAC).